2014
DOI: 10.5551/jat.19778
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor: A Cardinal Target for Atherosclerosis and Beyond

Abstract: LXRThe liver X receptor [LXR] was first discovered in 1995 as a new member of the nuclear receptor superfamily 1) and was subsequently found to be activated by oxygenated cholesterol derivatives 2) . Initially, this receptor was identified in tissue obtained from a rat liver 3) , with no known endogenous ligands, and was named LXR. Later, LXR was termed an 'adopted' nuclear receptor with the discovery of oxysterols 2) as endogenous ligands for this receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 109 publications
0
26
0
1
Order By: Relevance
“…LXRs, originally described as regulators, increase the expression of ABCA1 and RCT in ApoE -/ -knockout mice (Parikh et al, 2014). LXRa activation by synthetic activator T0901317 rescued reductions in ABCA1-mRNA and increased ABCA1 expression and apoA-I-mediated cholesterol efflux in the presence and absence of atorvastatin (Zhao et al, 2008;Qiu and Hill, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…LXRs, originally described as regulators, increase the expression of ABCA1 and RCT in ApoE -/ -knockout mice (Parikh et al, 2014). LXRa activation by synthetic activator T0901317 rescued reductions in ABCA1-mRNA and increased ABCA1 expression and apoA-I-mediated cholesterol efflux in the presence and absence of atorvastatin (Zhao et al, 2008;Qiu and Hill, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…49,50 There is a potential interaction or crosstalk between LXR and PPARγ. 39 We and others have shown that expression of PPARγ and/or other pro-lipogenic genes could reverse activated HSC to differentiated cells. 12,13,29 Wnt signaling is implicated in human fibrotic diseases, such as pulmonary fibrosis, renal fibrosis, and liver fibrosis.…”
Section: Plin5 Restores Ld Formation In Hscmentioning
confidence: 99%
“…Hepatic lipogenesis at transcriptional level is regulated by a group of protein regulators, including the transcription factor SREBP-1c, 48 as well as the nuclear receptors PPARγ, and LXR. 38,39 The activation of LXR activation stimulates lipogenesis via SREBP-1c. 49,50 There is a potential interaction or crosstalk between LXR and PPARγ.…”
Section: Plin5 Restores Ld Formation In Hscmentioning
confidence: 99%
“…94 The nuclear receptor superfamily members form both homodimers and heterodimers and likely act cooperatively to regulate nutrient metabolism and cardiometabolic risk. 95 Each of these highly specific receptors has diet-derived ligands; however, how seemingly divergent signals from each of these receptors respond to a meal remains unclear.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%